A systematic review of whether COVID‐19 randomized controlled trials reported on demographic and clinical characteristics. Issue 12 (5th October 2022) - Pak, Joyce; Lund, Jennifer L.; Keil, Alexander; Westreich, Daniel; Stürmer, Til; Wohl, David; Farel, Claire; Drummond, M. Bradley; Webster‐Clark, Michael
Abstract: Purpose: We aim to assess the reporting of key patient‐level demographic and clinical characteristics among COVID‐19 related randomized controlled trials (RCTs). Methods: We queried English‐language articles from PubMed, Web of Science, clinicaltrials.gov, and the CDC library of gray literature databases using keywords of "coronavirus, " "covid, " "clinical trial" and "randomized controlled trial" from January 2020 to June 2021. From the search, we conducted an initial review to rule‐out duplicate entries, identify those that met inclusion criteria (i.e., had results), and exclude those that did not meet the definition of an RCT. Lastly, we abstracted the demographic and clinical characteristics reported on within each RCT. Results: From the initial 43 627 manuscripts, our final eligible manuscripts consisted of 149 RCTs described in 137 articles. Most of the RCTs (113/149) studied potential treatments, while fewer studied vaccines (29), prophylaxis strategies (5), and interventions to prevent transmission among those infected (2). Study populations ranged from 10 to 38 206 participants (median = 100, IQR: 60–300). All 149 RCTs reported on age, 147 on sex, 50 on race, and 110 on the prevalence of at least one comorbidity. No RCTs reported on income, urban versus rural residence, or other indicators of socioeconomic status (SES). Conclusions: Limited reporting on race and other markers of SES make it difficult to draw conclusions about specific external target populations without making strong assumptions that treatment effects are homogenous. These findings highlight the need for more robust reporting on the clinical and demographic profiles of patients enrolled in COVID‐19 related RCTs.